(untitled) (Bangladesh Journal of Neurosurgery, 2023)
Focal cortical dysplasias (FCDs) belong to the large spectrum of malformations of cortical development (MCDs) and represent the most common structural brain lesion in children with drug-resistant focal epilepsies submitted to surgical treatment. It is responsible for nearly half of intractable epilepsy cases in children and adults, and at the same time it is characterized by quite good treatment outcome. We describe a case where a young girl had been suffering from intractable epilepsy and was on two medicines. She was operated upon and was relieved of her symptoms. Her histopathological examination revealed focal cortical dysplasia. We have to keep in mind that FCD can present as low grade glioma and treat it carefully. Bang. J Neurosurgery 2022; 12(1): 24-28